A GP130-Targeting Small Molecule, LMT-28, Reduces LPS-Induced Bone Resorption around Implants in Diabetic Models by Inhibiting IL-6/GP130/JAK2/STAT3 Signaling. (6th January 2023) - Liu, Qi-qi; Wu, Wei-wei; Yang, Jian; Wang, Rui-bin; Yuan, Ling-ling; Peng, Pei-zhao; Zeng, Mao-yun; Yu, Ke
Abstract : In this study, we examined the effect of the GP130-targeting molecule, LMT-28, on lipopolysaccharide- (LPS-) induced bone resorption around implants in diabetic models using in vitro and rat animal experiments. First, LMT-28 was added to osteoblasts stimulated by LPS and advanced glycation end products (AGEs), and nuclear factor- κ B receptor-activating factor ligand (RANKL) and associated pathways were evaluated. Then, LMT-28 was administered by gavage at 0.23 mg/kg once every 5 days for 2 weeks to type 2 diabetic rats with peri-implantitis induced by LPS injection and silk ligature. The expression of IL-6 and RANKL was evaluated by immunohistochemistry, and the bone resorption around implants was evaluated by microcomputed tomography. The results showed that LMT-28 downregulated the expression of RANKL through the JAK2/STAT3 signaling pathway in osteoblasts stimulated by LPS and AGEs, reduced bone resorption around implants with peri-implantitis, decreased the expression of IL-6 and RANKL, and decreased osteoclast activity in type 2 diabetic rats. This study confirmed the ability of LMT-28 to reduce LPS-induced bone resorption around implants in diabetic rats.